2011
DOI: 10.1097/wnn.0b013e31823fc1d0
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Cognitive Patterns in Schizophrenia and Methamphetamine Dependence

Abstract: Objective To examine whether overlapping cognitive deficits exist in currently drug-abstinent chronic methamphetamine (MA) abusers and schizophrenia (SZ) patients. Background Both SZ and chronic MA abuse are associated with frontostriatal disruption as well as deficits in cognitive control such as selective attention. To identify overlapping cognitive profiles, we compared performance of the two groups on the Stroop attention task. Method Data were analyzed from 69 MA abusers who had been MA-abstinent for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…The study of Jacobs et al (2008) revealed that patients with meth-induced psychotic disorder and those with paranoid schizophrenia have similar cognitive profiles. In contrast, Salo et al (2011) suggested that the cognitive functioning in meth users during the early stages of abstinence was worse than in patients with schizophrenia; furthermore, no correlation was found between their psychotic symptoms and task performance. However, previous studies have not considered the role of the duration of meth-induced psychosis on neurocognitive deficits.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The study of Jacobs et al (2008) revealed that patients with meth-induced psychotic disorder and those with paranoid schizophrenia have similar cognitive profiles. In contrast, Salo et al (2011) suggested that the cognitive functioning in meth users during the early stages of abstinence was worse than in patients with schizophrenia; furthermore, no correlation was found between their psychotic symptoms and task performance. However, previous studies have not considered the role of the duration of meth-induced psychosis on neurocognitive deficits.…”
Section: Introductionmentioning
confidence: 91%
“…The performance of METH + PP patients in most cognitive functioning domains was worse than that of their counterparts that did not experience persistent psychosis (METH − P and METH + BP) and the healthy control subjects. Several previous studies have reported that differentiating the clinical features of psychotic symptoms (Medhus et al, 2013;Srisurapanont et al, 2011) and cognitive profiles (Jacobs et al, 2008;Salo et al, 2011) between meth-related psychosis and schizophrenia can be challenging. Meth use may put users at a greater risk for developing psychotic symptoms.…”
Section: Cognitive Profiles Across Patient Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite similarities of the clinical manifestation between MAP and schizophrenia, few studies have addressed similarities and differences in the characteristics of prefrontal cortical dysfunction between the two disorders. A behavioral study reported that methamphetamine abusers in an early period of abstinence displayed greater attention deficits as indexed by Stroop interference effects than patients with schizophrenia (Salo, Ravizza & Fassbender ).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, it has been hypothesized that METH-induced changes in dopaminergic signaling involve a change in set point for drug reward that may represent an allostatic state contributing to vulnerability to relapse and re-entry into the addiction cycle (Koob 2000). It is, therefore, likely that the already observed dysfunction of prefrontal and limbic brain areas as well as fronto-striatal loops, which has repeatedly been reported in regular METH consumers (Chang et al 2007;Salo et al 2011;Bisagno et al 2016;Okada et al 2016), is also evident in their offspring. Given that cognitive functions mediated via the prefrontal cortex are highly predictive for school readiness, school success, job success, public safety, physical and mental health (Diamond 2013), it is likely that transgenerational effects are devastating for the upcoming generations and lead to strong societal problems.…”
mentioning
confidence: 93%